Tunneled Interpolated Flaps in the Reconstruction of Nasal Defects - Bonito,Frederico (2021)
Abstract The reconstruction of nasal skin defects is a challenge even for an experienced dermatological surgeon. When the defect is too large or complex to be corrected with simpler flaps, interpolated flaps are a good option, but they usually require two surgeries. Tunneled interpolated flaps were developed to allow the reconstruction of complex defects in only one surgical procedure. In nasal reconstruction, the main tunneled flaps are the paramedian forehead and the melolabial flaps. This review will focus on these two flaps: description of the technique, applications, advantages and disadvantages.